Dramatic response of FOLFIRINOX regimen in a collision pancreatic adenocarcinoma patient with a germline BRCA2 mutation: a case report. (15th October 2019) - Shimmura, Hideki; Kuramochi, Hidekazu; Jibiki, Norie; Katagiri, Satoshi; Nishino, Takayoshi; Araida, Tatsuo
Abstract: Germline BRCA1 and BRCA2 mutations are the most common gene mutations in familial pancreatic adenocarcinoma. Several reports have demonstrated the utility of platinum-based chemotherapy for treating cancer patients who harbour a BRCA mutation. Here we discuss a 47-year-old Japanese female with no relevant past history who presented with epigastralgia and fever in September 2016. A computed tomography scan revealed a low-density, low-enhanced tumour 15 mm in diameter in the head of the pancreas. The pathological diagnosis was a ductal pancreatic carcinoma. A 6 mm low-enhanced metastatic tumour was also detected in segment 4 of the liver. Because she had early onset of the disease and a family history—her mother died of pancreatic adenocarcinoma at age 48—we considered a diagnosis of familial pancreatic adenocarcinoma. She received modified FOLFIRINOX. Two months after starting chemotherapy, she was diagnosed with an invasive ductal carcinoma in the right breast. FOLFIRINOX was continued for 8 cycles (4 months); the primary pancreatic adenocarcinoma shrank and the liver metastatic foci disappeared, but the size of the breast tumour increased. Total right breast excision and sentinel lymph node dissection were performed. FOLFIRINOX was continued and after 12 cycles (6 months), both her pancreatic adenocarcinoma and liver metastasis were no longer visible using imaging. Pancreatoduodenectomy was performed and the primary tumour had shrunk to 2.5 mm. Genetic testing revealed a germline BRCA2 mutation. The FOLFIRINOX regimen showed dramatic effects on the collision pancreatic but not on the breast cancer. Abstract : A 47-year-old female with a germline BRCA2 mutation and family history of pancreatic adenocarcinoma was diagnosed with pancreatic adenocarcinoma, liver metastasis and breast cancer. The patient responded remarkably to FOLFIRINOX.